A MODEL FOR ADMINISTRATION OF THE STUDENT CARE AND SUPPORT SYSTEM IN SCHOOL UNDER THE OFFICE OF BANGKOK SECONDARY EDUCATIONAL SERVICE AREA 2 - Meemar, Weera; Pimsarn, Narong; Jenkwao, Sawien (Journal of Educational Review Faculty of Education in MCU, 2023)
The purpose of this research was to develop an administration model for the student care and support system in Schools under the Office of Bangkok Secondary Educational Service Area 2 conducted the research by studying quantitative data and qualitative data, divided into three steps as follows: 1) Study the problems and guidelines for the implementation the student care and support system in Schools under the Office of Bangkok Secondary Educational Service Area 2. 2) Develop and verify the administrative model of the student care and support system of secondary schools. and 3) Was to try and evaluate the administration model of the secondary school student care and support system. Qualitative data were collected by analyzing, synthesizing, interviewing. Quantitative data were collected using a questionnaire. Statistics used in data analysis were mean and standard deviation. The results of the study were as follows: 1) Implementation of the student care and support system in Schools under the Office of Bangkok Secondary Educational Service Area 2of the student care and support system administration process at a high level was the planning and implementation of the student support system at a high level, namely screening students. 2) Problems in the operation of the student care and support system in Schools under the Office of Bangkok Secondary Educational Service Area 2 of the student care and support system administration process the least problematic aspect was the planning and implementation of the student support system. The least problematic aspect is student screening. 3) Evaluation results of the administration model the student care and support system in Schools under the Office of Bangkok Secondary Educational Service Area 2 found that the assessment results of the model possibility and usefulness Overall, it was at the highest level.